Asian American athletes in sport and society - King, C. Richard 1968- (Routledge research in sport, culture and society, 2015)
For more than a century, sporting spectacles, media coverage, and popular audiences have staged athletics in black and white. Commercial, media, and academic accounts have routinely erased, excluded, ignored, and otherwise made absent the Asian American presence in sport. This book seeks to redress this pattern of neglect, presenting a comprehensive perspective on the history and significance of Asian American athletes, coaches, and teams in North America. The contributors interrogate the sociocultural contexts in which Asian Americans lived and played